PERAN MAHASISWA PSIKOLOGI ISLAM DALAM PENANGGULANGAN TRAUMA PASCA GEMPA - Reza Fahmi (Universitas Islam Negeri Imam Bonjol Padang, 2014)
Nobody wants tobe a victim of disaster, but they did no what will happen in the future. West Sumatera asan island with potentially has a problem about disaster. Instead of; an earthquick, flood, and Tsunami. Thisarticle will focus on State Institute for Islamic Studies students role for making mental rehabilitation after anerthquick in 2009.